2019
DOI: 10.1016/j.cedpsych.2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Prematurity and overlap between reading and arithmetic: The cognitive mechanisms behind the association

Abstract: It is well-known that very preterm children perform at lower levels than full-term children in reading and arithmetic at school. Whether the lower performance levels of preterm children in these two separate domains have the same or different origins, however, is not clear. The present study examined the extent to which prematurity is associated with the overlap (i.e., common variance) of reading and arithmetic among Finnish school beginners. We also examined the extent to which the association of prematurity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 56 publications
5
18
0
Order By: Relevance
“…In addition, the present study also gives useful insight into the relationship between linguistic and numeracy skills. As expected, there was a significant relationship between mean language scores and recognition and reading of digits (Purpura and Ganley, 2014;Korpipää et al, 2019), with phonological awareness playing a relevant role. Contrasting results were found regarding the relationship between phonological awareness and mathematical skills, and some authors have suggested that it might not be constant across development (Passolunghi et al, 2015).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In addition, the present study also gives useful insight into the relationship between linguistic and numeracy skills. As expected, there was a significant relationship between mean language scores and recognition and reading of digits (Purpura and Ganley, 2014;Korpipää et al, 2019), with phonological awareness playing a relevant role. Contrasting results were found regarding the relationship between phonological awareness and mathematical skills, and some authors have suggested that it might not be constant across development (Passolunghi et al, 2015).…”
Section: Discussionsupporting
confidence: 77%
“…However, there are contrasting results to this regard (for a review, see De Smedt et al, 2013), and some authors suggest that symbolic representation is more strictly related to mathematical achievements (Göbel et al, 2014;Goffin and Ansari, 2019). This is in line with the strong relationship found between math skills and language development (e.g., Korpipää et al, 2019), supporting the idea that language competence may act as a scaffolding ability on which numerical development may rely . In terms of linguistic skills, the verbal code proposed within the Triple Code Model (Dehaene, 1992(Dehaene, , 1997 was used in particular for counting, addition, and easy multiplication.…”
Section: Children's Cognitive Linguistic and Ans Skillsmentioning
confidence: 92%
“…These factors have been, in part, explored in other important work (e.g., Cirino, Childs, & Macdonald, 2018;Koponen et al, 2019;Korpipää et al, 2019). We controlled for one such factor, nonverbal cognitive abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is scant research on the developmental dynamics between reading and math, clues regarding the direction of the developmental effects may be drawn from a line of research that studies reading and math in conjunction. One line of studies have found that reading and math are correlated, however with no direct time‐dependent relations (e.g., Koponen, Aunola, Ahonen, & Nurmi, 2007; Koponen et al., 2019; Korpipää et al., 2017; Korpipää et al., 2019). This view is supported by the investment theory (Cattell, 1987).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation